Evaluation of Apple Pomace Flour Obtained Industrially by Dehydration as a Source of Biomolecules with Antioxidant, Antidiabetic and Antiobesity Effects - Stanislava Gorjanović; Darko Micić; Ferenc Pastor; Tomislav Tosti; Ana Kalušević; Slavica Ristić; Snežana Zlatanović (MDPI AG, 2020)
Apple pomace flour (APF) obtained at industrial scale level by the application of innovative technological process (dehydration (5 h, T ≤ 55 °C), grinding (300 µm)) was evaluated as a source of bioactive compounds with antioxidative, antiobesity and antidiabetic effects. Proximate composition, individual (HPLC-DAD-MS/MS) and total phenols (TPC) as well as flavonoids content (TFC), antioxidant (AO) activity (DPPH, ABTS, HPMC), water and oil holding capacity (WHC and OHC) of APFs obtained from apple pomace from mixed and individual apple cultivars grown conventionally and organically were compared. The effect of APF supplementation on the glycaemic status and glucose tolerance (oral glucose tolerance test (OGTT)) of C57BL/6J mice exposed to high-fat and sucrose diet was examined. High K content (4.2-6.4 g/kg), dietary fibres (35-45 g/100 g), TPC (4.6-8.1 mg GAE/g), TFC (18.6-34.6 mg QE/g), high water and oil holding capacity (4.7-6.4 and 1.3-1.6 g/g) were observed in the APFs. Content of major phenols (phlorizin, chlorogenic acid, quercetin), TPC and TFC correlated highly with prominent AO activity. APF supplementation lowered the increase of body weight gain and blood glucose, and improved glucose tolerance significantly. Health-promoting biomolecules, AO activity, functional properties and prevention of diet-driven glucose metabolism disorders pave the way to APF exploitation in human nutrition.